TEACHERS’ AND STUDENTS’ DIGITAL SKILLS DURING VIRTUAL TEACHING DEVELOPMENT. LAGUNA UNIVERSITY STUDY CASE (2013)
This article offers some of the results of an empirical research developed at University of La Laguna (Spain), the main idea was to understand both students and teachers real usage of ICT and to investigate about its influence in their digital teaching and learning processes in higher education. In order to manage this study’s development two independent questionnaires for 1561 students and 206 teachers who participated in the research. In this paper authors present only results mainly related to usage of ITC or digital skills of both teachers and students, in order to describe information about: search methods, communications development (e mail, forum use, instant messaging, social networking), accomplishing specific tasks: (use of different software, use of image edition software, use of video or audio editing software); entertainment activities (downloading music or movies); academy activities (use of collaborative work space, use of online classrooms); web participation activities (personal web page edition, management or use of other web sites and blogging).